Pengaruh Mathematics Anxiety dan Minat Belajar Terhadap Hasil Belajar Matematika - Anggraini, Silfia Ayu; Marhaeni, Nafida Hetty (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
The aim of this research is to determine the influence of mathematics anxiety and interest in learning on the mathematics learning outcomes of class VIII students at SMP Negeri 1 Sedayu. The population of this study was all students in class VIII of SMP Negeri 1 Sedayu. The sample was carried out using a simple random sampling technique, which found two classes totaling 64 students. This type of research is quantitative research with a survey method. Data collection techniques use questionnaires and documentation. The data were analyzed using normality tests, linearity tests, and multicollinearity tests. Data analysis techniques use simple regression analysis techniques and multiple regression analysis techniques. The results of the data analysis show that there is no influence of mathematics anxiety on mathematics learning outcomes. The results of the data analysis show that there is no influence of mathematics anxiety on mathematics learning outcomes. The relationship between variables is negative, meaning that the higher the anxiety experienced by students, the lower the students' mathematics learning outcomes. The results of the analysis of learning interest show that there is an influence of learning interest on mathematics learning outcomes. The relationship between variables is positive, meaning that the higher the student's interest in learning mathematics, the higher the student's mathematics learning outcomes. There is an influence between mathematics anxiety and interest in learning on students' mathematics learning outcomes, as evidenced by a significance value of 0.033 < 0.05. The coefficient of determination is 0,106, which shows the magnitude of the effective contribution simultaneously.